Pulmonary Complaints Among Gas Station Operators: A Descriptive Study in Klaten Region - Handayani, Sri; Agustiningrum, Ratna; Agustina, Nur Wulan; Haryanti, Rheni (Gaster, 2025)
Background Gas station environments pose a high risk for exposure to vehicle emissions, which may lead to respiratory health issues due to the accumulation of hazardous pollutants. Continuous exposure, particularly among gas station operators, increases susceptibility to pulmonary disorders. Objective This study aimed to describe the prevalence and characteristics of pulmonary complaints among gas station workers in the Klaten region. Methods A descriptive study was conducted at two gas stations (44.57406 and 44.57403), both located on major traffic routes and operating daily. The total sampling technique was employed, involving 51 workers. Data were collected using structured questionnaires that assessed personal characteristics, smoking habits, mask usage behavior, and respiratory symptoms. Descriptive statistics using frequency distribution were applied in the data analysis. Results Findings showed that 41.2% of respondents experienced pulmonary complaints. The most frequently reported symptoms included shortness of breath while walking briskly, shortness of breath after physical exertion, productive cough, and persistent coughing throughout the day. Contributing factors identified were long working hours, smoking behavior, and inconsistent use of face masks. Conclusion A significant proportion of gas station operators reported respiratory complaints potentially linked to prolonged exposure to vehicle emissions. Additional risk factors such as smoking and improper personal protective equipment use may further compromise respiratory health. These findings underscore the need for preventive measures, including occupational health education, routine screening, and environmental interventions.